PENELITIAN KUANTITATIF DALAM PENDIDIKAN AGAMA ISLAM: TELAAH KONSEPTUAL, KARAKTERISTIK, MODEL, DAN RAGAM - Nafaisal Ulumi; Sayidatur Rohmah; Ifa Zumrotin; Mashfufatur Rohmah; Nashrullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This research aims to conceptually examine quantitative research in Islamic Religious Education (PAI), including its definition, characteristics, models and varieties, as well as its application in Islamic education research. This research uses a qualitative approach with the type of library research. Data was obtained through the study of various books, research methodologies, and articles in national and international journals relevant to quantitative research and Islamic education. The analysis is carried out through the identification, selection, categorization, and synthesis of various concepts and research findings related to the focus of the study. The results of the study show that quantitative research has the main characteristics in the form of the use of numerical data, structured instruments, objectivity, testing of validity and reliability, use of samples, statistical analysis, generalization ability according to research conditions, and systematic research design. Quantitative research models can be grouped into non-experimental research, such as descriptive, comparative, correlational, survey, and ex post facto, as well as experimental research that includes true experiments, quasi experiments, and single-subject experiments. In the context of PAI, quantitative approaches are relevant to examine the relationships, differences, and effectiveness of educational learning and innovation. However, its application needs to pay attention to the complexity of religious values, morals, and experiences so that the quantification process remains in accordance with the characteristics of the research object.